Caracterização de extratos de própolis e efeito sobre Campylobacter termotolerantes de origem avícola - Calazans, Luíza Toffano Seidel (2020)
Thermotolerants Campylobacter are related to a group of pathogens that are carried by food and are currently considered as the main ones of global occurrence and with high frequency of resistance to antimicrobials. From the above, the present study aimed to identify biocomposites present in four extracts of green and red propolis and to evaluate alternatives regarding the antimicrobial potential. Extracts from Brazil, obtained by conventional ethanol extraction and extraction assisted by ultrasound, were evaluated. Four cultures of collections and twenty-five isolates from three species (Campylobacter jejuni, Campylobacter coli and Campylobacter lari) comprised the study. The technique used was microdilution in broth in a 96-well plate, which allowed the analysis of eleven concentrations of the propolis extracts (0.01 to 100 mg / mL-1). Variability was observed for antimicrobial activity. Greater microbial viability and motility were identified by optical microscopy at the highest concentrations of propolis tested. In addition, regarding the effect on bacterial viability of red propolis in relation to green propolis, the red one showed more efficient. There was no difference in extraction methods. It is concluded that the propolis extracts had an unsatisfactory antimicrobial effect, as well as a cellular protective effect for high concentrations in this study, regardless of the extraction method, which may have a desirable connotation for laboratory diagnosis.